2010
DOI: 10.1016/j.bpj.2010.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Stiffening of Human Skin Fibroblasts with Age

Abstract: Changes in mechanical properties are an essential characteristic of the aging process of human skin. Previous studies attribute these changes predominantly to the altered collagen and elastin organization and density of the extracellular matrix. Here, we show that individual dermal fibroblasts also exhibit a significant increase in stiffness during aging in vivo. With the laser-based optical cell stretcher we examined the viscoelastic biomechanics of dermal fibroblasts isolated from 14 human donors aged 27 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 44 publications
4
60
1
1
Order By: Relevance
“…Relating to senescent cells, it has been described that SHDF in vitro are much larger with round and flat appearance compared to that of HDF, produce higher amounts of vimentin and also exhibit decreased adhesion to substrate, because of a lower expression of vinculin and the presence of small focal contact sites [13,14]. All these characteristics have been seen in our SHDF used in this work in contrast to primary HDF cells, which show higher expression of vinculin, more prominent focal adhesion contacts and high production of extracellular matrix proteins, including Col1 and fibronectin ( Figs 5-7), and therefore with increased ability for movement compared with SHDF [14,27]. In addition, Schulze et al [27] found an increase in stiffening with age in HDF cells obtained from human donors that could be related with changes in the organization and density of the extracellular matrix, particularly with alterations in the polymerization state and organization of actin in the cell (balance between G and F-actin).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Relating to senescent cells, it has been described that SHDF in vitro are much larger with round and flat appearance compared to that of HDF, produce higher amounts of vimentin and also exhibit decreased adhesion to substrate, because of a lower expression of vinculin and the presence of small focal contact sites [13,14]. All these characteristics have been seen in our SHDF used in this work in contrast to primary HDF cells, which show higher expression of vinculin, more prominent focal adhesion contacts and high production of extracellular matrix proteins, including Col1 and fibronectin ( Figs 5-7), and therefore with increased ability for movement compared with SHDF [14,27]. In addition, Schulze et al [27] found an increase in stiffening with age in HDF cells obtained from human donors that could be related with changes in the organization and density of the extracellular matrix, particularly with alterations in the polymerization state and organization of actin in the cell (balance between G and F-actin).…”
Section: Discussionmentioning
confidence: 64%
“…All these characteristics have been seen in our SHDF used in this work in contrast to primary HDF cells, which show higher expression of vinculin, more prominent focal adhesion contacts and high production of extracellular matrix proteins, including Col1 and fibronectin ( Figs 5-7), and therefore with increased ability for movement compared with SHDF [14,27]. In addition, Schulze et al [27] found an increase in stiffening with age in HDF cells obtained from human donors that could be related with changes in the organization and density of the extracellular matrix, particularly with alterations in the polymerization state and organization of actin in the cell (balance between G and F-actin). Thereby, whereas young primary cells showed relatively higher amounts of unpolymerized G-actin, the SHDF cells exhibited apparently shorter and thicker actin stress fibres because of their relatively lower levels of G-actin and higher levels of F-actin.…”
Section: Discussionmentioning
confidence: 65%
“…Maintaining adequate skin fl exibility and elasticity is a primary defense against mechanical damage. Aging decreases the skin's fl exibility and elasticity, increasing susceptibility to mechanical damage [ 5 ] .…”
Section: Mechanisms and Impact Of Stratum Corneum Damagementioning
confidence: 99%
“…It is well known that cell mechanics plays an important role in various cellular functions [1][2][3][4], and in many disease-related mutations, especially for carcinogenesis [5]. Besides, it was also demonstrated that cell's mechanical properties can be used as an intrinsic and reliable marker to distinguish between different cell types [6,7].…”
Section: Introductionmentioning
confidence: 99%